Comparison of skull growth in two ecosystem modifiers: beavers Castor canadensis (Rodentia: Castoridae) and muskrats Ondatra zibethicus (Rodentia: Cricetidae) - Segura Gago, Alda Valentina (2023)
Beavers and muskrats are semi-aquatic, generalist herbivorous rodents regarded as invasive in southern South America, with high impacts on the ecosystem. They share some morphological characters of the skull, but different body sizes and phylogenetic history, showing evident shape differences in young and adult skulls during the development in both species. Considering their similar ecological specializations, skull shape could be achieved through different or similar patterns of allometric growth during ontogeny. We analyzed quantitatively the ontogenetic series including 94 specimens of beavers and muskrats and performed multivariate and bivariate analyses considering 20 linear measurements. Our main results from the different approaches suggest high differences in the ontogenetic trajectories of beavers and muskrats, implying disparity in the muscular, functional, and structural conditions of the skull of both species. These differences reflect that although skulls might undergo similar mechanical stress, it is possible to reach a cranial morphology compatible with the similar behavioral and ecological specializations between both species from patterns of skull development that are markedly different.